Thai EFL Pre-service Teachers’ Challenges in Teaching English in Indonesian Classrooms - Mamat, Mr Hilman (AL LUGHAWIYAAT, 2022)
The purpose of this qualitative study is to explore the challenges Thai EFL pre-service teachers faced during their field teaching practice at some schools. This study used a reflective journal as the instrument to collect the data gathered data was analyzed thematic. The findings showed that there were several challenges Thai EFL fac in their field of teaching practice in Indonesian classrooms. First, they are not confident to speak English while teaching English in an Indonesian classroom. Second, some of the Indonesian students did not focus to study English while the Thai pre-service teachers were teaching in the classroom. Last, some Thai pre-service teachers encountered problems with managing limited time in classroom management. This study implies that EFL student teachers may understand the sources cause challenges. They should prepare before the true field of teaching will become